Production and Financial Networks in Interplay - Huremović, Kenan; Jiménez, Gabriel; Moral-Benito, Enrique; Peydró, José-Luis; Vega-Redondo, Fernando (American Economic Review, 2026)
We show that bank shocks to firms propagate along the production network with stronger upstream than downstream effects. Our identification relies on (i) administrative datasets from Spain covering supplier-customer transactions and bank loans, (ii) bank credit supply shocks from the global financial crisis, and (iii) a general equilibrium model of a production network with financial frictions, estimated structurally. We find network propagation amplifies the impact of bank shocks on GDP growth by nearly 50 percent. Moreover, bank shocks to firms’ distant suppliers and customers contribute similarly to this aggregate effect as bank shocks to firms’ direct customers and suppliers. (JEL D22, D85, E23, G01, G21, G32, L14)